Personal Hygiene dengan Kejadian Penyakit Kulit - Apriyana Irjayanti; Anton Wambrauw; Ida Wahyuni; Ayu Anisa Maranden (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Skin disease is a disease that attacks the surface of the body and is caused by various diseases. Skin diseases can also be caused by fungi, germs, viruses and parasites. The purpose of this study was to determine the relationship between personal hygiene and the incidence of skin diseases. This type of research uses an analytic observational method with a cross sectional research design. The population in this study were 149 residents, samples taken from the entire population were 149 respondents. The sampling technique uses total sampling. Collecting data using questionnaires and observation. The data analysis used was univariate analysis and bivariate analysis, using the chi-square test (α<0.05). The results of the study show an overview of the incidence of skin disease from 149 respondents who suffer from skin disease (67.1%). The description of personal hygiene (skin cleanliness, hand hygiene, clothing cleanliness, and use of towels) from 149 respondents (89.3%) was not good. The results of personal hygiene research obtained p-value = (0.000). The conclusion is that there is a relationship between personal hygiene and the incidence of skin diseases. For Community Health Centers to increase efforts to prevent and control skin diseases by increasing the socialization of clean and healthy living behaviors to support public health.